2009
DOI: 10.3399/bjgp09x472674
|View full text |Cite
|
Sign up to set email alerts
|

Identification and management of familial hypercholesterolaemia: what does it mean to primary care?

Abstract: Familial hypercholesterolaemia is one of the most common dominantly inherited disorders to be identified in primary care, leading to raised serum cholesterol evident from the first year of life. Around 1 in 500 people are affected by this condition, but less than 15% of these are currently attending lipid clinics, suggesting that the vast majority are unrecognised in general practice. The recently released National Institute for Health and Clinical Excellence evidencebased guideline on the identification and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 14 publications
0
44
0
2
Order By: Relevance
“…Sin embargo, este enfoque es controversial, ya que múltiples entidades 8,[29][30][31] recomiendan un cribaje selectivo, a realizarse sólo en grupos de alto riesgo.…”
Section: Discussionunclassified
“…Sin embargo, este enfoque es controversial, ya que múltiples entidades 8,[29][30][31] recomiendan un cribaje selectivo, a realizarse sólo en grupos de alto riesgo.…”
Section: Discussionunclassified
“…A coronary event in a family member can increase the perception of risk and the willingness of relatives to be subsequently tested for FH. Screening in primary care should employ an initial non-fasting lipid profile [8], which should be undertaken opportunistically, based on family history of hypercholesterolaemia and premature CVD (age < 60 years) [27,28]. FH screening should also be offered to all patients with tendon xanthomata and premature arcus cornealis [6][7][8][9]22].…”
Section: Detection Of Index Cases: Screening For Fhmentioning
confidence: 99%
“…The research data show that only 15% of patients with FH can do regular medical visits [4], the vast majority of patients fail to achieve the lipid control objectives, or because of side effects, stains cannot be used at a standard treatment …”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…A series of research evidence indicated that among the patients with CHD before the age of 55 patients, 5% of them accompanied with FH [4]. The risk of FH patients with CHD increased 3.5 -16 times compared to patients without FH, and serious gene mutations in homozygous patients are the decisive factors that increase the risk of cardiovascular disease (CVD) [17].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%